Vertical and Horizontal Proportions of the Face and their Correlation to Phi in a South Indian Population - Crystal R. Soans; Karishma A. Mathew; M. Subramanya Ravi; K. Gauthami; Shalin Shersha (Indian Journal of Dental Research)
Background: With the shift in focus from the hard to soft tissue in orthodontic diagnosis and treatment planning, the scope of orthodontic treatment has grown beyond achieving an ideal occlusion, also to achieve ideal aesthetic facial proportions. Since time immemorial, the various horizontal and vertical proportions of an ideal face is considered to follow the golden/divine ratio. Aim: The aim of this study is to assess the vertical and horizontal proportions of the face and their relation of phi in males and females of Dakshina Kannada population. Materials and Methods: The study was carried out on 100 subjects, which included 50 males and 50 females, aged between 18 and 30 years. Photographs were taken under standardized condition and adjusted to a standardized image size (5″ × 4″). Adobe Photoshop CS5.1 software was used for making all the measurements. A total of 11 vertical and horizontal ratios were independently measured for males and females, and their relation to phi was assessed. The data were subjected to Shapiro–Wilk test for testing the normality. Homogeneity of variance assumption was tested by using Levene statistic homogeneity of variance. One sample t test was used for the comparison between phi and mean vertical and horizontal ratios in males and females. Results: In males and females of the Dakshina Kannada, a statistically significant correlation was seen between all the horizontal and vertical facial proportions and phi (p < 0.05). Between male and female groups, a significant difference was noted in the intertemporal/intercanthal ratio, interalae/nose width and Intereye-soft menton/ala-soft menton (p < 0.05). Conclusion: Golden proportion can be used as a guideline in orthodontic treatment planning. However, it should not be the decisive factor in determining the facial attractiveness.